Domestic Consumer Awareness of Energy Consumption Practices in Pakistan - Hanif, Muhammad Wasif; Hafeez, Shakir; Shah, Syed Afzal Moshadi; Iqbal, Naveed (International Journal of Energy Economics and Policy, 2021)
Electricity waste is a bottleneck in availing clean, green, uninterrupted, and sustainable electricity supply. The synthesis of the studied literature portrays that irresponsible behavior indulges consumers to take irresponsible action, which leads to electricity waste and crisis. Therefore, to get the know-how of irresponsible behavior, this study aims to investigate the role of awareness concerning electricity consumption, wastage, gadget efficiency, and conservation. A questionnaire-focused survey was carried out to collect data and performed descriptive analysis to critically evaluate the data. The results explicate that consumers possess a low level of wasteful consumption awareness and “lack-of-information” is a big issue in waste management. Thus, the study concludes that unawareness is the key determinant that creates and strengthens a sense of irresponsibility in consumer behavior. The academician and practitioners need dire attention to take precautionary measures for developing prominent awareness campaigns and strategic policy guidelines to distort irresponsible human nature by including fearful promotional contents in marketing campaigns. Keywords: Electricity Awareness, Electricity Conservation, Electricity Efficiency, Electricity Waste, Irresponsible Behavior, Electricity Crisis JEL Classifications: Q4, Q40, D1 DOI: https://doi.org/10.32479/ijeep.11441